Established and Nascent Entrepreneurs: Comparing the Mental Health, Self-Care Behaviours and Wellbeing in Singapore - Gong, Jiankun; Xu, Zezheng; Wang, Sherry Xueli; Gu, Mingyan; Ong, PuayChin; Li, Yuanzhe (Frontiers in Sociology, 2022)
Mental health problems currently affect a quarter of the world’s population. Recent research in western societies has started to examine the relationship between entrepreneurship and mental health problems such as Attention Deficit Hyperactivity Disorder (ADHD) and dyslexia. However, little has been done to categorise entrepreneurs into different types and investigate how their levels of mental health and well-being correspond to these types. This study divided entrepreneurs into established and nascent categories and examined this topic in Singapore. By distributing two sets of surveys, a total of 834 responses were collected, with 346 responses from established entrepreneurs and 488 responses from nascent ones. The results showed that the nascent entrepreneurs’ levels of well-being were found to be much lower than those of the established entrepreneurs. Furthermore, entrepreneurs with ADHD or dyslexia symptoms generally had a much lower level of life satisfaction, compared with those without. However, the self-care behaviours observed in this sample differed somewhat from observations made in western societies, which might be explained by the different cultures and habits in Singaporean society. The findings not only highlight the need for relevant organisations to support nascent entrepreneurs but serve to remind veteran entrepreneurs to practise more healthy self-care behaviours.